Konsep Islamic Spiritual Entrepreneurship dalam Surat An-Nur Ayat 37 - Dadang; Diniyah, Fellasufah; Ramadhani, Febri (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
The concept of Islamic entrepreneurship has been widely studied and developed by practitioners and academics. However, there are still differences in the concepts offered. The purpose of this study is to offer a new concept of Islamic Spiritual Entrepreneurship based on (Q.S; An-Nur, 24:37). The method used in this study is a literature study. The data used are from the Qur'an, Tafsir Al-Misbach, books, journals. The results of this study indicate that Islamic spiritual entrepreneurship must always instill in oneself to remember Allah, prioritize worship, zakat-infaq-alms, and remember death. If all of this can be implemented, you will achieve success in the world and happiness in the afterlife